Strategi Penyelesaian Kasus Aturan Ketenagakerjaan: Studi Kasus Bentrok Karyawan di PT Gunbaster Nickel Industry - Nathasya Femi Ekarista; Muhamad Rizal; Sari Usih Natari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
PT. Gunbaster Nickel Industry has had violations of labor regulations that have resulted in the deaths of three workers since 2022. Some of the violations that this company has committed are wage deductions, a contract status system for permanent jobs, unilateral layoffs, wage deductions, and violations of Occupational Health Safety (K3). The actions taken by the employees involved clashing with the union by going on strike. The method used in this study is qualitative and is closely related to observation and secondary data collection. The research process was carried out based on secondary data by collecting data from relevant sources. The author gives suggestions to solve this problem in a tripartite way. This approach is considered beneficial because it is through transparent and open dialogue. All parties can express interests and reach sustainable solutions. Based on the explanation above, the appropriate solution to the problem is the tripartite method. This is because this approach creates fair deals, protects employee rights, promotes harmonious working relationships, and supports business continuity. With the collaboration of all parties, tripartite creates solutions that meet the interests of all parties involved.